Student with special needs and mathematics learning: A case study of an autistic student - Sabaruddin, Sabaruddin; Mansor, Rosnidar; Rusmar, Irfan; Husna, Fadila (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2020)
The provision of mathematics for autistic students has not gained a special concern. In fact, many autistic children have good mathematical skills and some are even excellent. It imposes teachers to formulate and create effective strategies to teach autistic students. The purpose of this study was to determine teacher behavior and how to teach students with autism effectively. This study was designed as a qualitative case study research. It involved mathematics teacher, assistant teacher, student, and parents. Data were obtained through observations and interviews. The autistic student's attitude and behaviors during mathematics learning were investigated. It included examinations on the supporting and inhibiting factors in mathematics learning in a school for students with special educational needs/SLB. The result indicated that mathematics learning for students with autism as performed in inclusive education was different from regular education programs, in which teachers were required to adjust materials with students' psychological condition. It also revealed that the students had had focus issues; hence materials were mostly conveyed outside the lesson plan, particularly to introduce the basic material. The supporting factors included parents' motivation for the student to learn and behave appropriately and well-designed learning packages. Meanwhile, limited learning media and school facilities, as well as the absence of special teachers for students with autism, became the inhibiting factors for mathematics learning.